Privatisation and Organisational Performance: A case Study of Umeme Kabale District, Uganda. - Richard Kanyima, Rugumayo (Kabale University, 2020)
The study thought to investigate the impact of privatization on organizational performance of UMEME, in Kabale Municipality, Uganda. The researcher used cross-sectional and descriptive study designs with both qualitative and quantitative approaches. A sample of 357 was chosen from the target population. Data was collected using questionnaires and interviews and analyzed using percentages and frequencies. The study findings indicated that there was political influence, fluctuating power supply due to fall in water levels, power theft and delayed connectivity of new customers. The researcher recommended that, proper policy should be put in place on how to build the customers’ faster connectivity and a standby generator or solar plant to handle power shortage.